Cellulose nanorods in liquid crystalline elastomers for improved actuators - Pontes, Rita Valério (2015)
Nanotechnology plays a central role in ‘tailoring’ materials’ properties and thus improving its performances for a wide range of applications. Coupling nature nano-objects with nanotechnology results in materials with enhanced functionalities. The main objective of this master thesis was the synthesis of nanocrystalline cellulose (NCCs) and its further incorporation in a cellulosic matrix, in order to produce a stimuli-responsive material to moisture. The induced behaviour (bending/unbending) of the samples was deeply investigated, in order to determine relationships between structure/properties. Using microcrystalline cellulose as a starting material, acid hydrolysis was performed and the NCC was obtained. Anisotropic aqueous solutions of HPC and NCC were prepared and films with thicknesses ranging from 22μm to 61μm were achieved, by using a shear casting technique. Microscopic and spectroscopic techniques as well as mechanical and rheological essays were used to characterize the transparent and flexible films produced. Upon the application of a stimulus (moisture), the bending/unbending response times were measured. The use of NCC allowed obtaining films with response times in the order of 6 seconds for the bending and 5 seconds for the unbending, improving the results previously reported. These promising results open new horizons for building up improved soft steam engines.